STRATEGI PEMBELAJARAN BAHASA ARAB BERBASIS HEMISPHERIC BRAIN FUNCTION UNTUK PESERTA DEWASA - Erta Mahyudin; Hanik Mahliatussikah; Parihin (Universitas Islam Negeri Mataram, 2026)
This study evaluates the implementation of Arabic language teaching strategies for adult learners at the LBIQ DKI Jakarta using the theoretical framework of hemispheric brain function. A qualitative descriptive approach was employed, incorporating interviews, classroom observations, questionnaires, and literature analysis. Data were analysed thematically through coding, categorisation, and triangulation across multiple sources. The findings reveal that instruction at this institute remains predominantly traditional, relying on grammar-translation method, which primarily activate left-hemisphere functions, while underutilising the right hemisphere’s roles in creativity, intuition, and contextual understanding. Consequently, adult learners truggle to apply Arabic communicatively. This study recommends integrating right- and left-brain functions through a multisensory approach that incorporates visualisation, contextual simulation, and interactive technology to enhance retention, confidence, and both receptive and productive language skills. The proposed strategic framework offers practical guidance for non-formal institutions and enriches Arabic language pedagogy by applying neuroplasticity and andragogical principles to design adaptive instruction tailored to adult learners.